Ectopic Compound Odontoma in the Buccal Mucosa: Report of a Rare Case - Aparna Venigalla; Leela Krishna Guttikonda; Hasini Nelakurthi; Suresh Babburi; Soujanya Pinisetti; Ajay Banerji Kotti; Lavanya Kalapala (Hindawi Limited, 2015)
Eruption of tooth into extraosseous locations is an extremely rare condition. We report a case of a six-year-old girl child with tooth-like structure erupting from the right buccal mucosa. Clinical, radiographic, and histopathologic examination suggested the diagnosis of compound odontoma. Very few cases have been reported so far, where tooth has been located completely in the soft tissue and a variety of names have been used for that condition. A brief review of the literature and the ambiguity in naming the situation is discussed.